Analisis Efisiensi Waktu Siklus Untuk Meningkatkan Produktivitas Dengan Line Balancing Pada Proses Pengemasan Produksi Obat Diabetes di PT.OPQ - Agustinus Yunan; Dimas Anjar Wijanarko (Journal of Industrial and Engineering System, 2022)
Operation Excelence is needed at manufacturing process in order to achive optimum cost. One of method is using line balancing. It work by increasing efficiency and remove bottole neck at workstation.. The purpose of this research is to increase productivity in the work path of diabetes drug production line, it means that all work stations can achieve optimum output, eliminate or reduce material accumulation by identifying line balances at work stations. By using the Line Balancing method. The method used is the Ranked Position Weight (RPW) heuristic method. As result productivity was increasing, with line efficiency from 58.36% to 80.25%, balance delay from 41.64% to 19.75%, a decrease in the amount of material accumulation between work stations on the diabetes drug production trajectory from 25 - 1175 doos / hour to 4 - 174 doos / hour, and eliminating the bottleneck on the trajectory of diabetes drug production.